ACCESS MANAGEMENT AND QUALITY OF DISTANCE EDUCATION IN NIGERIA Abdullahi Nimota Jibola Kadir - AbdullahiNimota Jibola Kadir (PJDOL, 2023)
TThe study investigated the relationship between Canvas learning management system, Google Classroom, Zoom for online teaching and quality of distance education. Purposive sampling technique was used to select 750 lecturers in 75 centres of Open University of Nigeria. Data was collected usingAccess Management and Quality of Distance Education Questionnaire. Pearson product moment correlation coefficient and linear regression analysis were used to analyse the data collected. The findings revealedthat Canvas learning management system, Google Classroom and Zoom for online teaching were positive and significantlycorrelated with quality of distance education. It was recommended that lecturers should continue making use of canvas learning management system so as to helps students to plan the process of their learning. Also, lecturers should continue to adopt and implement the use of google classroom to facilitate effective teaching and learning in order to provides learning opportunities by encouraging questions, exploration and outliers. Furthermore, lecturers should continue make use of zoom for online teaching so as to helps students to work in groups as well ashelps students to collaborate both on the preparation and recording of the presentation through video conferencingin order to achieve quality of distance education in Nigeria.